2019
DOI: 10.1021/acs.est.9b02637
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Seawater Surfactants Associated with Primary Marine Aerosol Particles Produced by Bursting Bubbles at a Model Air–Sea Interface

Abstract: Surfactants account for minor fractions of total organic carbon in the ocean but can significantly influence the production of primary marine aerosol particles (PMA) at the sea surface via modulation of bubble surface tension. During September and October 2016, model PMA (mPMA) were produced from seawater by bursting bubbles at two biologically productive and two oligotrophic stations in the western North Atlantic Ocean. Total concentrations of surfactants extracted from mPMA and seawater were quantified and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 60 publications
(105 reference statements)
1
62
0
Order By: Relevance
“…The surface monolayer model predictions suggest surfactant concentrations on the order of several tens to 100 mM, consistent with reported atmospheric concentrations, are required to substantially affect N d (i.e., modify SS c by >20%). These predictions highlight the necessity of a more comprehensive understanding of the types and concentrations of surfactants in aerosol, as to date only a few studies in a few environments have been reported (7,8,10,29,46,47). Global simulations of N d have only rarely incorporated such surface partitioning models (5,6), in part because partitioning effects had not been experimentally confirmed until this work.…”
Section: Discussionmentioning
confidence: 99%
“…The surface monolayer model predictions suggest surfactant concentrations on the order of several tens to 100 mM, consistent with reported atmospheric concentrations, are required to substantially affect N d (i.e., modify SS c by >20%). These predictions highlight the necessity of a more comprehensive understanding of the types and concentrations of surfactants in aerosol, as to date only a few studies in a few environments have been reported (7,8,10,29,46,47). Global simulations of N d have only rarely incorporated such surface partitioning models (5,6), in part because partitioning effects had not been experimentally confirmed until this work.…”
Section: Discussionmentioning
confidence: 99%
“…Continued focus on primary marine aerosol fluxes is needed to extend the strong foundation of work by several investigators over the region that has raised new questions into factors such as surfactant properties (Frossard, Gérard, et al, ), characterization of physicochemical properties and fluxes of primary marine aerosol over the full spectrum of aerosol sizes (Keene et al, ), and further consideration of the various factors affecting fluxes (e.g., biogeochemical and physical processes in sea water, time of day and season, and characteristics at the air‐water interface) to improve source functions. The nature and role of organics enriched in marine aerosols also warrants further examination owing to subsequent impacts on radiative and hygroscopic properties of the aerosol, and also general multiphase photochemical processing in the MBL (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Continued focus on primary marine aerosol fluxes is needed to extend the strong foundation of work by several investigators over the region that has raised new questions into factors such as surfactant properties (Frossard, Gérard, et al, 2019), characterization of physicochemical properties and fluxes of primary 10.1029/2019JD031626…”
Section: Disciplinary Researchmentioning
confidence: 99%
“…It is well-known that surface tension is an important parameter in the activation of aerosol particles into cloud droplets and that surface-active organic species can contribute to the depression of surface tension compared to that of pure water. [1][2][3][4][5][6] It is also well-established that surface tension equilibrium can take a long time to be achieved and may involve several dynamic stages, such as reorganization and phase transitions in the surface layer following the initial surface adsorption. [7][8][9][10][11] Such dynamic effects are currently not accounted for in atmospheric cloud and droplet models.…”
Section: Introductionmentioning
confidence: 99%